Timing of urinary catheter removal after colorectal surgery with pelvic dissection: A systematic review and meta-analysis. (January 2022) - McIntosh, Stuart; Hunter, Ross; Scrimgeour, Duncan; Bekheit, Mohammed; Stevenson, Lynn; Ramsay, George
Abstract: Background: Urinary catheters are routinely placed before colorectal surgery. Enhanced recovery after surgery (ERAS) recommends their removal as soon as possible. However, premature removal risks urinary retention, and delayed removal increases risk of urinary tract infections (UTIs). This meta-analysis aims to synthesise the published literature on the optimal timing of urinary catheter removal following colorectal surgery with pelvic dissection. Materials and methods: The protocol for this meta-analysis is registered on PROSPERO (CRD42019150030).Pubmed, Ovid and Web of Science databases were searched (January 2020). Primary outcomes included urinary retention and catheter associated UTI. The intervention was removal of urinary catheter following colorectal surgery with pelvic dissection on postoperative days 1–2 (early); 3–4 (intermediate); or 5+ (late). Meta-analysis was performed using Comprehensive meta-analysis V2. Results: Eight papers were analysed. 883 patients had early catheter removal, 236 intermediate and 204 late. Early catheter removal was associated with increased risk of urinary retention when compared to late removal RR = 2.352 95% CI = 1.370–4.038 (p = 0.002). No significant difference in urinary retention was found between early and intermediate or intermediate and late catheter removal groups. Early catheter removal was associated with reduced risk of UTIs compared to late removal RR = 0.498, 95% CI 0.306–0.811, (p = 0.005). No significant difference in UTIs was found between early and intermediate or intermediate and late catheter removal groups. Conclusions: Removal of urinary catheters on postoperative day 3–4 provides a balance between minimising the risks of urinary retention and UTIs. This analysis can be used to finesse future ERAS protocols concerning catheter removal in colorectal surgery involving pelvic dissection Highlights: The removal of urinary catheters on postoperative day 3–4 provides a balance, minimising the risk of urine retention and UTIs. Early removal of urinary catheters after pelvic colorectal surgery is associated with increased risk of urinary retention. Leaving urinary catheters in for 5 days or more, increases urinary tract infection risk.